Priority Strategy Of Tourism Development Of Siau Tagulandang Biaro Island Regency - Jozef Raco (Jurnal Manajemen, 2024)
The recovery of the tourism industry requires the Siau Tagulandang Biaro Islands Regency to reevaluate its strategy by identifying critical development priorities. That is the aim of the study, which applies the Analytic Hierarchy Process (AHP) and fuzzy-AHP methods. The analysis would serve to identify the key factors and establish strategic recommendations. The results show that facilities are the highest criterion (thirty-four point seven per cent AHP; thirty-four point four per cent Fuzzy-AHP). The global weight calculation shows that Maintaining the ecosystem and cleanliness of beaches/lakes/hot springs are priority elements (eight point six per cent AHP; eight point five per cent Fuzzy-AHP). The sensitivity analysis shows that the results could be more robust, consistent, and stable. These results indicate no significant difference between the AHP and Fuzzy-AHP methods. The tourism development strategy for Siau Tagulandang Biaro Regency must prioritise improving the cleanliness and health of tourist destinations. This research answers an essential problem for the Siau Islands Regency government, Tagulandang Biaro.